Brand, Service Quality, and Product Quality Towards Customers Purchasing Decisions at PT. Wahana Jaya Raya Medan - Joni; Arvin; Nicholas Anderson; Nurmaidah Ginting (Jurnal Mantik, 2021)
This study aims to determine the effect of brand, service quality, and product quality towards customers purchasing decisions. This type of research is explanatory research. The entire population is 127respondents. Due to a large population, the sampling technique will be reduced by using the Slovin formula with an error tolerance level of 5% so that there are as many as 96 respondents in the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis, and the coefficient of determination as well as simultaneous test, and partial test. The results showed that brand, service quality, product quality partially, andsimultaneously have a positive, and significant effect on purchasing decisions. Based on the results of this study, the implications for management are to further improve the brand, service quality, and product quality.